The Effect of 30 Minutes of Light Walking on Decreasing Blood Sugar Levels in Elderly People with Type 2 Diabetes Mellitus (Dukuh Village, Gondang District, Tulungagung Regency): Pengaruh Jalan Kaki Ringan 30 Menit Terhadap Penurunan Kadar Gula Darah Pada Lansia Penderita Diabetes Melitus Tipe 2 (Desa Dukuh Kecamatan Gondang Kabupaten Tulungagung) - Ria Eki Widyastuti; Nurhidayati Nurhidayati; Wiwid Yuliastuti; Suciati Suciati (JOURNAL OF MEDICAL AND HEALTH SCIENCE, 2024)
Nutrition is important factor in process of growth and development children. Toddler groups that are susceptible nutrition status are children aged 1-3 years. The optimal nutrition status can control the child's gross motoric milestone. This study aims to determine correlation of nutrition status with gross motoric milestone of children aged 1-3 years in Posyandu I Pojok Village Campurdarat District Tulungagung Regency. The research was conducted on March 9, 2017. This research is quantitative research using correlation analytic design with cross sectional approach. The population this research are 35 children aged 1-3 years registered in Posyandu I Pojok Village Campurdarat District Tulungagung Regency. The sample research is 30 children aged 1-3 years with Purposive Sampling technique. Data collection using DDST II observation sheet. Data were analyzed using Spearman test. Result of this research got most have normal nutrient status with normal gross motoric milestone as many as 13 respondents (43,3%) from 20 respondents (66,7%). Spearman statistic test got value ρ = 0,01 < α = 0,05 so H0 rejected and H1 accepted, where there is correlation between nutrition status with gross motoric milestone of children aged 1-3 years in Posyandu I Pojok Village Campurdarat District Tulungagung Regency. This research shows there is correlation between nutrition status and gross motoric milestone of children aged 1-3 years. Therefore it expected parents can more attention nutrition intake of the child by monitoring nutrition status regularly, so that if nutrition status of children is good, then child’s gross motoric milestone can be optimal.